Voeg die daad by die Woord. Diensleer en teologiese onderrig. - Van den Berg, J-A (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Service learning and theological education. The Faculty of Theology at the University of the Free State is advertised in the media with the phrase “Voeg die Daad by die Woord”. This phrase is in line with the core essence of theology as well as with the new development of Service Learning within the tertiary education context. Service Learning is a new approach in the lecturing of theology in higher education. Although new to the domain of theological education, Service Learning embodied the core essence and values of theology. In developing a Doing Theology, contextualized within the culturally multi-layered African landscape, accent is placed in the article on an engagement with the other and his /her world. In describing this process of Doing Theology the concept of participation plays an important role. By using some of the principles within narrative theory the author describes how in an engaged participation with each other amongst other, previously marginalised people/groups, can become co- researchers in the research process. By applying the research methodology of Participatory Action Research, researchers and co-researchers are being in a multilateral way empower to learn by service. By participating in this way not only leads to the formation of new meaningful identities, but also to the eruption of opportunities for enriched learning through service.